Fabrication of promising Cu-Al-Ni alloys by electron-beam additive manufacturing - Moskvichev, Evgeny N. (AIP Conference Proceedings)
The samples of the promising Cu-Al-Ni alloys were fabricated by electron-beam additive printing and studied by electron microscopy. The fabrication was carried out using the combined powder feed and wire feed technology. The samples obtained by specific selecting the printing regime, varying the degree and mode of post-processing, were characterized by homogeneous chemical composition structure. The microstructure and elements distribution of the obtained material was determined by scanning electron microscopy. In the case of printing without additional electronbeam treatment, an irregularity of the microstructure, chemical composition, precipitation of intermetallic phases was observed.